Filum terminale arteriovenous shunt with nidus structure: a report of rare condition and treatment consideration. (4th May 2023) - Xu, Jian-Kun; Ye, Ming; Yu, Jia-Xing; Zhang, Hong-Qi
Abstract: Background: In the literature, filum terminale arteriovenous shunts (FTAVSs) always feature a single shunt point. Nidus-type FTAVSs have rarely been reported, and the best treatment strategy is unclear. This is a report of one exceptional case of a nidus-type FTAVS and surgical treatment of the lesion. Case description: The patient suffered from cauda equina syndrome for 9 months. Magnetic resonance imaging and spinal angiography revealed a nidus-type FTAVF at the L2 level. Surgical resection was performed in the hybrid operating room, and the nidus was completely resected with the assistance of intraoperative methylene blue angiography and neurophysiological monitoring. The postoperative neurological function was stable. Conclusions: A nidus-type arteriovenous shunt could originate from the FT, and in such cases, complete surgical resection with intraoperative neurophysiological monitoring in a hybrid operating room should be suggested.